Improving the Efficiency of X-ray Data Management through Database-Based Web Application at RSUD I Lagaligo - Musdy Yusuf; M. Hasanuddin; Muh. Hajar Harike; Abdul Malik; Suharsono Bantun (Program Studi Teknik Komputer, 2024)
The development of information technology in the health sector encourages BLUD RSUD I Lagaligo East Luwu Regency to improve the efficiency of X-ray data management. This research aims to develop a web-based x-ray result database application to speed up access and increase user satisfaction. The methods used include requirements analysis, system design, application development with Laravel and MySQL, as well as functionality testing and User Acceptance Testing (UAT). The results showed that data access time was reduced from 7 minutes to 1 minute and user satisfaction increased from 3.4 to 4.8. This application is proven effective in improving the efficiency and quality of radiology services. Suggestions for further research are integration with broader hospital information systems and development of advanced analytic features.